2017
DOI: 10.1111/jth.13621
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant soluble apyrase APT102 inhibits thrombosis and intimal hyperplasia in vein grafts without adversely affecting hemostasis or re‐endothelialization

Abstract: Summary Background Occlusion of vein grafts (VGs) after bypass surgery due to thrombosis and intimal hyperplasia (IH) is a major clinical problem. Apyrases are enzymes that scavenge extracellular ATP and ADP and promote adenosine formation at sites of vascular injury and hence have potential to inhibit vein graft pathology. Objectives We examined the effects of recombinant soluble human apyrase, APT102, on platelets, smooth muscle cells (SMCs), and endothelial cells (ECs) in vitro and thrombosis and IH in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additional studies are required to determine if activation of neutrophil occurs before their binding to the injured endothelium and to identify the signaling pathway explaining how down-regulation by adenosine could prevent the accumulation of neutrophils at the site of injury. Y. Ji et al have reported that systemic administration of a recombinant apyrase inhibits thrombosis smooth muscle cell migration and intimal hyperplasia in vein grafts without increasing bleeding or compromising re-endothelialization (22). To confirm that point, additional experiments are required to decipher the role played by (ATP-activated) neutrophils in hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are required to determine if activation of neutrophil occurs before their binding to the injured endothelium and to identify the signaling pathway explaining how down-regulation by adenosine could prevent the accumulation of neutrophils at the site of injury. Y. Ji et al have reported that systemic administration of a recombinant apyrase inhibits thrombosis smooth muscle cell migration and intimal hyperplasia in vein grafts without increasing bleeding or compromising re-endothelialization (22). To confirm that point, additional experiments are required to decipher the role played by (ATP-activated) neutrophils in hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“… 45 The elimination-phase half-life is ∼36 h in mice. 46 Animals were injected with 1 mg/kg of APT102 (APT Therapeutics, Inc., St. Louis, MO) by tail vein injection before the initial isoflurane induction. 47 Vehicle-treated animals received tris-buffered saline as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, there were no safety or toxicity concerns when APT102 treatment was protracted after resolution of colitis in vivo (115). Additional studies reported on the safety profile of this molecule in the vascular setting (116,117). However, since CD39 also plays an important role in tumor development and progression (99,(118)(119)(120)(121) and inhibition of effector immune responses against pathogens (99,122,123), the safety of long-term treatments aimed at restoring the levels of this ectoenzyme in the context of autoimmune diseases should be considered and carefully evaluated.…”
Section: New Immunotherapiesmentioning
confidence: 99%